Analysis of Promotional Media Selection Based on Modified Analytical Hierarchy Process to Increase Halal Products Sales Volume - Andarwati, Mardiana; Swalaganata, Galandaru (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
This study identified promotional media that used Analytical Hierarchy Process (AHP) in previous experiments. The data collection process used to carry out this study presented considerable challenges. This was due to the extensive questionnaire data obtained from MSMEs in halal products. Therefore, a binary rating system was employed to simplify the questionnaire, with 1 and 0 assigned to consideration and contempt, respectively. The EPIC model, which contained four distinct dimensions, was used to produce valuable indicators and allowed measurements within each EPIC dimension. The main focus of this study was the development of AHP modifications that are showed in the calculation of pairwise comparison matrices. The data collection process was much easier and faster because the questionnaire was simple and only took less than 2 minutes. The result showed that social media can effectively substitute traditional advertising in the scenarios mentioned. The most popular alternative for promotion for MSMEs is social media (36%), followed by search engines (30%) and products collaboration (13%).